Gone Viking : a travel saga - Arnott, Bill (Rocky Mountain Books Incorporated, 2020)
To "go Viking" is to embark on an epic journey. For more than eight years, Bill Arnott journeyed throughout the northern hemisphere, discovering sites Scandinavian explorers raided, traded, and settled? finding Viking history in a wider swath of the planet than most anthropologists and historians ever imagined.